Approximated observation operator‐based ℓq regularisation algorithm for SAL imaging. Issue 14 (1st July 2017) - Wang, Ning; Wei, Zhonghao; Li, Guangzuo; Wang, Ran; Zhang, Keshu; Wu, Yirong
Abstract : The synthetic aperture ladar (SAL) is similar to the synthetic aperture radar (SAR) while working at optical frequency, which could provide higher resolution than SAR. However, due to the shorter wavelength, the vibration of the platform and atmosphere turbulence will induce more serious phase error, which results in the defocused SAL image with lower signal‐to‐noise ratio. A novel approximated observation operator‐based imaging method for SAL is proposed to solve an ℓq norm optimisation problem. Combined with the motion compensation method, the presented ℓq regularisation algorithm can suppress the side lobe and clutter, and improve the target‐to‐clutter ratio and image contrast efficiently. Also, the computational complexity is the same as the matched filtering imaging algorithm. Real airborne SAL data has been used to demonstrate the feasibility of the proposed algorithm.